Cartografias de um corpo – existência e resistência em pauta. - Vaz, Henrique Maia Lins (2014)
The mind is an idea of the body and the bodies make of the "sense" the ultrasense: they are an overtaking of the "sense", since there are no fewer things in the mind that exceed our consciousness than there are things in the body that exceed our knowledge. A body is material, dense, impenetrable, it is not empty, it is filled with other bodies, but also filled with itself... A body extends and each side of it touches and is touched by other bodies: bodies intersecting each other, rubbing, squeezing, wrapping each other or striking each other...: they trade so many signals, callings, warnings, that no defined "sense" can be depleted. A body is, furthermore, imaterial... It is a drawing, an outline, an idea. The creation of Bodies without Organs indicate an ethical valorization of the "intensive", a valorization that does not underestimate the urgency of a certain practical prudence. Another way to define a body is from its power to affect and to be affected... Cartographing implies a toiling on a terrain that carries certain playfulness, where the imagination is source for knowledge, if not the only one… Cartography of speed and slowness between unformed elements, or mapping compositions of the intensive corresponding affections: longitudes and latitudes of a body. The present work aims at apprehending the potencies of the body to parallelly unfold the potencies of the mind that escape the consciousness, all in the company of "intercessors" that corroborate to a conceptual multiplicity in a rhizomatic manner which affirms the life, where neither the existence is put as guilty nor the will feels guilty by existing itself. Resistance is the act of creation, accurately it is taken as the fight against the "entropy", once the nature tends to it, heading to the disintegration, disinformation and forgetfulness... Resistance whereas it refuses the encoded and preestablished modes of manipulation and telecommand; an existential singularization that coincides with a taste of living, a "form-of-existence". The ornamentum, the adornment while "generic activity" of humankind, the "instrumental physicality", the "corporeity of the interpreter", the "physiology of the sound", the "cartography of gestures", the "kludge as luthiery", the "time as ornament", the "interpretation" as the sum of the physical conditions for the sound apparition and the "happening"..., intimate mean of the sense, composes the fulcrum of this work in an apprehension of "composing" that is not officium, but therapeutic, therapy that is founded on affective dynamics, being strictly personal, refusing by all means the creation of a normative ethics…The "partitural" is territory, matrix where the encoded, choreographed and indicated are the periodicity, the velocity, the direction and the nature of gestures: the kinetics of the bodies... In this work, there is not a pursuit to rear a new order, or Truth, it is not about the model to be a scope, the body urges qua sentinel that keeps us vigilants about the limits of the conscience - searching in the body the radicalness of the thought, such is the creative act of this research.